Exploring how local cultural influences affect tourist conduct - Hidayat, Indra Iryanto Nur; Wisnalmawati, Wisnalmawati; Sugandini, Dyah (Asian Journal of Islamic Management (AJIM), 2023)
Purpose – The primary aim of this study is to investigate the influence of local culture on the behavioral intentions of Muslim tourists who have visited Kebondalem Kidul Cultural Tourism Village through the mediation of memorable tourism experiences and destination image.Methodology – In this study, a quantitative analysis approach and descriptive analysis were employed, utilizing a 5-point Likert scale: the sample collection non-probability sampling method, specifically convenience sampling. The sample comprised 190 respondents who had experienced the Kebondalem Kidul Cultural Tourism Village as a tourist destination. Structural Equation Modeling (SEM) SmartPLS 3.2.9 was used as the analytical tool for analysis.Findings – The study reveals that local culture directly impacts Muslim tourists' recommendation intention, memorable tourism experience, and destination image when they visit Kebondalem Kidul Cultural Tourism Village.Implications – This research aims to aid Tourism Village managers in crafting effective marketing strategies and provides valuable insights for Kebondalem Kidul Cultural Tourism Village managers in addressing Muslim tourist needs.Originality – This study contributes substantially to the existing body of knowledge regarding Local Culture in multiple aspects. Initially, it investigated the Local Culture variable, specifically in the context of heritage tourism, with a primary emphasis on tourists who were patrons of the Kebondalem Kidul Cultural Tourism Village.